2013
DOI: 10.1111/infa.12030
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Infants' Bimanual Reaching Patterns is Related to the Onset of Upright Locomotion

Abstract: Infants typically exhibit a shift from unimanual to bimanual reaching toward the end of their first year, which has been linked to walking onset. Until now, however, it has been unclear whether it was the onset of walking per se that influenced reaching patterns or whether a more general shift to an upright posture might have prompted the reorganization of the motor system. To address this question, the current study longitudinally chronicled the uni‐ and bimanual reaching preferences of 25 infants every 3 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 78 publications
0
4
0
1
Order By: Relevance
“…Thurman et al (2012) observed that the timing of the increase in bimanual reaching in six infants followed longitudinally was more in in line with the onset of standing alone than walking per se . And, Atun-Einy et al (2014) found that increase in bimanual reaching began to show a small rise when infants began cruising. Thus, there may be several reasons for our lack of finding of the predicted significant increase in bimanual reaching in the novice walker group.…”
Section: Discussionmentioning
confidence: 97%
“…Thurman et al (2012) observed that the timing of the increase in bimanual reaching in six infants followed longitudinally was more in in line with the onset of standing alone than walking per se . And, Atun-Einy et al (2014) found that increase in bimanual reaching began to show a small rise when infants began cruising. Thus, there may be several reasons for our lack of finding of the predicted significant increase in bimanual reaching in the novice walker group.…”
Section: Discussionmentioning
confidence: 97%
“…The ability to interact with objects with both hands is critical for the performance of more complex exploratory behaviors, such as fingering and manipulation, to gather more detailed information about objects. 42 Early bimanual holding is also an important precursor for essential future activities, including feeding, dressing, and writing. Bimanual abilities have not been well studied in young populations at risk despite the fact that a lack of midline movement has been shown to relate to future impairments in motor and cognitive abilities.…”
Section: Infants Born Ptbi Had Impaired Bimanual Abilitiesmentioning
confidence: 99%
“…Variability has historically been considered noise in developmental studies, but it is becoming increasingly accepted as a normal and even essential part of typical development. 42,49 By exploring a range of behaviors and relationships among their bodies and objects, infants may acquire both new action possibilities and knowledge. For example, behavioral variability is required for learning important early, foundational skills, such as postural control, and this behavioral variability is diminished in infants with movement impairments.…”
Section: Variability Of Exploratory Behavior In Infants Born Preterm mentioning
confidence: 99%
“…For example, postural development seen in unsupported sitting can facilitate skills associated with more complex vocalization productions such as increased syllable production per breath and greater control of utterance production (Yingling, 1981 ). In some cases, therefore, new possibilities in the vocal system may be nested within other motor milestones; the skill of unsupported sitting or any other action capability may have important consequences for future actions across all systems (Reed, 1982 ; Turvey, 1992 ; Gibson and Pick, 2000 ; see e.g., Nickel et al, 2013 ; Atun-Einy et al, 2014 ; Koterba et al, 2014 ). Therefore, in the current study, we consider how specific motor and language milestones might have “cascading effects” (Koterba et al, 2014 ) on the development of other skilled and controlled behaviors.…”
Section: Introductionmentioning
confidence: 99%